2015
DOI: 10.1167/15.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Updating visual working memory in the change detection paradigm

Abstract: An updating version of a visual change detection paradigm was used to investigate the behavioral outcomes and event-related potential (ERP) correlates of visual working memory updating. In each trial, participants were either presented with a memory array followed by a test probe, or with two successive memory arrays. Participants were instructed to update their working memory with the information in the second array. The second array differed from the first one in all, some, or none of the items. When a subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
7
6
0
Order By: Relevance
“…The ability to recognize a matched probe depended only on whether that item was repeated or updated, regardless of what happened with the other items in WM. This finding is in line with previous studies (Kessler et al, 2015). Along with Experiments 1 and 2, our results demonstrate that changes in topological properties affected the representation in VWM, indicated by a weakened repetition-benefit effect.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The ability to recognize a matched probe depended only on whether that item was repeated or updated, regardless of what happened with the other items in WM. This finding is in line with previous studies (Kessler et al, 2015). Along with Experiments 1 and 2, our results demonstrate that changes in topological properties affected the representation in VWM, indicated by a weakened repetition-benefit effect.…”
Section: Resultssupporting
confidence: 93%
“…The four conditions exhibited no significant main effect, F(3, 45) ¼ 0.499, p ¼ 0.685, g p 2 ¼ 0.032. This result is similar to the finding of a previous study (Kessler et al, 2015). As expected, two memory arrays did not increase the difficulty of the task, and all participants could remember the first memory array carefully as required.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Removing irrelevant information frees WM capacity. The evidence supporting removal of noncued items from WM converges with the finding that visual WM's contents can be flexibly discarded to encode new, more up-to-date information on an item basis (Kessler et al, 2015), and with evidence for the removal of outdated information as a component of updating of verbal WM . 4.…”
Section: Interim Summarysupporting
confidence: 57%
“…Particularly, the amplitude of P3b subcomponent with a peak latency of~450 ms increases when the current memory representation is modified by new information (Polich 2007). Recent studies, however, showed an earlier updating effect in the lateralized ERP components:~200 -300 ms (Kessler et al 2015). Thus, repetition suppression and memory updating predict different effects of refixation in the postsaccadic interval: whereas the former should be reflected in amplitude decrease at earlier latencies, the latter should be reflected in amplitude increase at latencies after 200 ms.…”
Section: Introductionmentioning
confidence: 96%